Characterization of pigeonpea lipoxygenase in response to Fusarium udum infection* - MANDAL, A K; SINHA, P (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2005–07 to characterize lipoxygenase activity in pigeonpea in response to Fusarium udum infection. Four known resistant genotypes, viz ‘ICP 87119’, ‘ICP 8863’, ‘BDN 2’ and ‘BSMR 736’ have shown consistently higher lipoxygenase (LOX) activity in comparison to susceptible genotypes viz ‘Bahar’ and ‘TTB 7’. The pH optima for LOX activity were at pH 6–6.5, 7.5 and 9.0 exhibited by 3 distinct peaks. Peaks at pH 6– 6.5 and 7.5 were almost similar in both resistant and susceptible genotype. Peak of higher activity at pH 9.0 was significantly different in resistant in comparison to susceptible genotype. It indicated that pigeonpea LOX system may have at least 3 different isoforms and had substrate preference on linoleic acid. Difference in kinetic parameters like, Km values, catalytic efficiency and selectivity in purified enzyme has supported the differential kinetic behaviour in resistant and susceptible genotype.